Perancangan User Interface Dan User Experience Fitur Customer Relationship Management (CRM) Pada Aplikasi Krealogi dengan Metode Design Thinking - Yusup, Maulana; Nugroho, Imam Ma'ruf; Alam, Syariful (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
At this time the Krealogi application wants to create a new feature, namely the Customer Relationship Management feature, with Customer Relations it is expected to be able to help provide a means to make it easier to connect with customers so that customers are more generous to Micro, Small and Medium Enterprises (MSME), but currently Krealogi does not have a suitable application design. user friendly to their target users. From the basis of this problem the author will design a user interface and user experience Customer Relationship Management that is user friendly with the design thinking method and for testing using the single ease question method. After testing the respondents, it was found a score of 6.5 which means that the value of the UI designed is quite easy for users to use.